(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2016)
The work is devoted to modeling of landslide slopes and methods of determining the shear strength. Three types of physical and geological models have been distinguished. Based on the results of experimental studies, changes in the formula of the slopes stability assessment have been proposed regarding to slopes composed of clayey soils of solid, semi-solid and tight plastic consistency, where the total value of the cohesion is to be reduced by the value of the hard cementation cohesion. Clay soils of soft plastic and liquid plastic consistency are capable to viscous-plastic and plastic deformations, so that on the slopes, composed of such soils, landslides on the mechanism of formation are plastic landslides or landslide flows. Taking into account that the sliding surface zone has no solid structural links in the formula of evaluating the slope stability the shear strength value should be taken as τ_f=σ φ․